2007
DOI: 10.2134/jeq2006.0541
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Speciation of Sequential Extracts of Organic Amendments Using Nuclear Magnetic Resonance and X‐ray Absorption Near‐Edge Structure Spectroscopies

Abstract: The chemical forms of phosphorus in organic amendments are essential variables for proper management of these amendments for agro-environmental purposes. This study was performed to elucidate the forms of phosphorus in various organic amendments using state-of-the-art spectroscopic techniques. Anaerobically digested biosolids (BIO), hog (HOG), dairy (DAIRY), beef (BEEF), and poultry (POULTRY) manures were subjected to sequential extraction. The extracts and residues after extraction were analyzed by solution (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
65
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 48 publications
7
65
1
1
Order By: Relevance
“…Similar overestimation of inorganic P in H 2 O-P has been reported by other authors (Ajiboye et al, 2004(Ajiboye et al, , 2007. However, while Ajiboye et al (2004Ajiboye et al ( , 2007 determined organic P as the difference between P measured by the inductively couple plasma atomic emission spectroscopy (ICP-AES) and molybdate blue method, organic P in this study was determined as the difference between molybdate blue measured P in digested and undigested P extract. Acid digestion of extract and the subsequent neutralization of the digest for molybdate blue P determination could also interfere with P measurement in the digested sample especially if the concentration of organic P is very low.…”
Section: Sequential Fractionation Of Fecal and Manure Phosphorussupporting
confidence: 84%
See 3 more Smart Citations
“…Similar overestimation of inorganic P in H 2 O-P has been reported by other authors (Ajiboye et al, 2004(Ajiboye et al, , 2007. However, while Ajiboye et al (2004Ajiboye et al ( , 2007 determined organic P as the difference between P measured by the inductively couple plasma atomic emission spectroscopy (ICP-AES) and molybdate blue method, organic P in this study was determined as the difference between molybdate blue measured P in digested and undigested P extract. Acid digestion of extract and the subsequent neutralization of the digest for molybdate blue P determination could also interfere with P measurement in the digested sample especially if the concentration of organic P is very low.…”
Section: Sequential Fractionation Of Fecal and Manure Phosphorussupporting
confidence: 84%
“…Inorganic P (NaOH-Pi) constituted between 16 and 61% of P extracted by NaOH in the feces, and between 26 and 69% of P extracted in the manure. Turner and Leytem (2004) reported 59% of hog manure NaOH-P as inorganic while Ajiboye et al (2007) reported 79% as inorganic P. The wide variation in percent NaOH-Pi among the various dietary treatments was due to the presence or absence of supplemental inorganic P with NaOH-Pi decreasing with decreasing supplemental inorganic P (Table 4). It is possible that inadequate supply of P prevented the reaction of phosphate with cations such Al, Ca, Mg and Fe.…”
Section: Sequential Fractionation Of Fecal and Manure Phosphorusmentioning
confidence: 99%
See 2 more Smart Citations
“…This shows that even in the organic fertilizer treatments, P was accumulated mainly in inorganic forms, due to the high inorganic P levels that are already present in animal manures (Cassol et al, 2001;Koopmans et al, 2003;McDowell & Stewart, 2005) or because of the rapid enzymatic hydrolysis after soil application (He et al, 2008). Ajiboye et al (2007) showed that in alkali extract of cattle manure, 92 % of total P belonged to the orthophosphate category and only 5 % to monoester and 3 % to the diester category. In poultry litters, orthophosphate accounted for only 43 % of total P, monoester for 51 % (47 % in phytic acid) and diester for only 6 %.…”
Section: Accumulated Phosphorus Formsmentioning
confidence: 99%